1999
DOI: 10.1016/s0009-9236(99)70077-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the gene in relation to dextromethorphan -demethylation capacity in a Japanese population

Abstract: The CYP2D6 allele frequencies in our Japanese subjects differed from those determined in previous studies of white subjects or mainland Chinese subjects. Individuals homozygous for *10 who have relatively low in vivo CYP2D6 activity represent almost 20% of the Japanese population. In addition, we did not identify any subjects with amplified *2 among our 98 Japanese men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
74
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 21 publications
7
74
1
Order By: Relevance
“…An IM phenotype is usually observed in populations harboring a combination of one CYP2D6 null allele and another allele with impaired expression and/or function, such as CYP2D6*10 (Zanger et al, 2004). The frequency of PMs is 5 to 10% in the Caucasian population and less than 1% in the Asian population (Sohn et al, 1991;Dahl et al, 1992;Tateishi et al, 1999). Among the variant alleles reported thus far, CYP2D6*3, CYP2D6*4, CYP2D6*5, and CYP2D6*6 account for approximately 97% of the PM alleles in the Caucasian population (Sachse et al, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An IM phenotype is usually observed in populations harboring a combination of one CYP2D6 null allele and another allele with impaired expression and/or function, such as CYP2D6*10 (Zanger et al, 2004). The frequency of PMs is 5 to 10% in the Caucasian population and less than 1% in the Asian population (Sohn et al, 1991;Dahl et al, 1992;Tateishi et al, 1999). Among the variant alleles reported thus far, CYP2D6*3, CYP2D6*4, CYP2D6*5, and CYP2D6*6 account for approximately 97% of the PM alleles in the Caucasian population (Sachse et al, 1997).…”
mentioning
confidence: 99%
“…The catalytic properties of CYP2D6*10 and CYP2D6*2 have been studied extensively in vivo and in vitro using recombinant expression systems and reaction phenotyping. The frequency of CYP2D6*10 is relatively high in Asians, and individuals with an IM phenotype and with CYP2D6*10/*10 or CYP2D6*10/*null genotypes, respectively, exhibit lower catalytic activities toward typical CYP2D6 substrates such as dextromethorphan (Tateishi et al, 1999), metoprolol , and nortriptyline (Yue et al, 1998) than wild-type homozygous individuals. Subjects harboring CYP2D6*2/*2 exhibit metabolic activity similar to that of wild-type individuals for various substrates (Johansson et al, 1993; The purpose of this study was to investigate the functional characterization of the CYP2D6 variants identified in Japanese subjects.…”
mentioning
confidence: 99%
“…Despite the very low frequency of poor metabolizers of CYP2D6 in Asian populations, these groups actually display lower mean CYP2D6 activity than Caucasians with the reference allele CYP2D6*1. This reduced activity is represented by a right shift in the metabolic ratio (parent/ metabolite ratio) for several CYP2D6 substrates, including debrisoquine (Kalow et al, 1980), sparteine (Droll et al, 1998), metoprolol (Horai et al, 1989), and dextromethorphan (Tateishi et al, 1999). This lower overall CYP2D6 activity has been attributed to the high frequency in the Asian populations of a reduced activity variant of CYP2D6, i.e., CYP2D6*10.…”
mentioning
confidence: 99%
“…However, the remaining two alleles that are detected by the protocol and confer reduced levels of metabolism are common in African and Oriental Asian populations. In published datasets for Asian populations CYP2D6*10 ranges from 40% in Japanese [44] to 70% in Taiwanese Chinese [45]; CYP2D6*17 ranges in published datasets for African populations from 9% in Ethiopians [46] to 34% in Zimbabweans [47]. The genotypic information that the protocol provides can be used in conjunction with known CYP2D6 allele frequencies in different ethnic groups as a guide to deciding which other polymorphisms should be characterized, depending on whether a study is concerned with identifying URM or IM phenotypes.…”
Section: Resultsmentioning
confidence: 99%